Effect of N-Feruloylserotonin and Methotrexate on Severity of Experimental Arthritis and on Messenger RNA Expression of Key Proinflammatory Markers in Liver - Pašková, Ľudmila; Kuncírová, Viera; Poništ, Silvester; Mihálová, Danica; Nosáľ, Radomír; Harmatha, Juraj; Hrádková, Iveta; Čavojský, Tomáš; Bilka, František; Šišková, Katarína; Paulíková, Ingrid; Bezáková, Lýdia; et al. (Journal of immunology research, 2016)
Rheumatoid arthritis (RA) is a chronic inflammatory disease, leading to progressive destruction of joints and extra-articular tissues, including organs such as liver and spleen. The purpose of this study was to compare the effects of a potential immunomodulator, natural polyphenol N-feruloylserotonin (N-f-5HT), with methotrexate (MTX), the standard in RA therapy, in the chronic phase of adjuvant-induced arthritis (AA) in male Lewis rats. The experiment included healthy controls (CO), arthritic animals (AA), AA given N-f-5HT (AA-N-f-5HT), and AA given MTX (AA-MTX). N-f-5HT did not affect the body weight change and clinical parameters until the 14th experimental day. Its positive effect was rising during the 28-day experiment, indicating a delayed onset of N-f-5HT action. Administration of either N-f-5HT or MTX caused reduction of inflammation measured as the level of CRP in plasma and the activity of LOX in the liver. mRNA transcription of TNF-α and iNOS in the liver was significantly attenuated in both MTX and N-f-5HT treated groups of arthritic rats. Interestingly, in contrast to MTX, N-f-5HT significantly lowered the level of IL-1β in plasma and IL-1β mRNA expression in the liver and spleen of arthritic rats. This speaks for future investigations of N-f-5HT as an agent in the treatment of RA in combination therapy with MTX.
Keywords: játra; methotrexát; Serotonin; C-reaktivní protein; serotonin; regulace genové exprese; cytokiny; Organ Specificity; Methotrexate; Time Factors; krysa rodu Rattus; Biomarkers; zvířata; časové faktory; arachidonátlipoxygenasy; artritida experimentální; biologické markery; Gene Expression Regulation; Liver; stupeň závažnosti nemoci; Male; transkriptom; Cytokines; Severity of Illness Index; Transcriptome; Rats; Animals; Inflammation Mediators; mužské pohlaví; orgánová specificita; mediátory zánětu; C-Reactive Protein; Disease Models, Animal; Arthritis, Experimental; Arachidonate Lipoxygenases; modely nemocí na zvířatech